New species of Myrmicine ants from Western Australia(Hymenoptera: Formicidae) - Shattuck, Steven O. (Zootaxa, 2007)
Three new species belonging to the ant subfamily Myrmicinae are described from Western Australia. Epopostruma inornata is the nineteenth species known for this Australian genus. It has been collected only once. Mayriella occidua is the eighth species of this small genus, and the sixth from Australia. It is the first species from Western Australia and extends the known distribution of the genus into south-western Australia. Mesostruma spinosa is the fifth species, out of nine known for the genus, to be found in Western Australia. It has been collected only once.